PENGARUH PEMBERIAN EDUKASI PSIKOSPRITUAL TERHADAP TINGKAT KECEMASAN PASIEN PRE OPERASI DI RSUD DRS.H.ABU HANIFAH BANGKA TENGAH TAHUN 2023 - Mulyadi, Asep; Fitri, Nurwijaya; Permatasari, Indah (Institut Kesehatan dan Teknologi Al Insyirah, 2023)
Anxiety disorders are the most common mental illnesses. Spiritual therapy is one of the efforts carried out in nursing care to address discomfort or anxiety. Spiritual care, in addition to medications and other medical treatments, is a means of involving religion through prayer and remembrance, which are aspects of healing or deep psychotherapy aimed at developing selfconfidence in patients and, most importantly, fostering optimism. The aim of this research is to determine the effect of psychospiritual education on the level of preoperative patient anxiety. The research design is pre-experimental with a one-group pretest-post-test design in the Orchid and Ashoka rooms at RS H. Abu Hanifah Bangka Tengah, with a total sample size of 24 respondents. Sampling was done using purposive sampling technique. The research resultsshow that after receiving psychospiritual education, anxiety levels significantly decrease with a value of p = 0.001. Based on the research findings, individuals experiencing anxiety should receive nursing care that includes spiritual support therapy. Keywords: anxiety, psychospiritual education, preoperative Keywords: Anxiety, psychospiritual education, Preoperative